Metformin Exhibits Anti‐Inflammatory Effects by Regulating microRNA‐451/CXCL16 and B Cell Leukemia/Lymphoma 2 in Patients With Osteoarthritis - Nahid Alimoradi; Amin Ramezani; Mohammad Tahami; Negar Firouzabadi (ACR Open Rheumatology)
Objective Osteoarthritis (OA) is the most common cause of chronic disability in joints among older individuals. The primary goal of OA treatment is pain relief to improve the quality of life. Inflammation and aging are involved in the pathogenesis of pain in OA. In this study, we evaluated the ability of metformin to regulate microRNAs, such as miR‐451 and miR‐15b, and their target proteins, CXCL16 and B cell leukemia/lymphoma 2 (BCL‐2), involved in inflammation and apoptosis. Methods In this double‐blind placebo‐controlled clinical trial, patients were randomly divided into two groups: one receiving metformin and the other receiving a placebo for four months (starting at 0.5 g/day for the first week, increasing to 1 g/day for the second week, and increasing to 1.5 g/day for the remaining period). In addition to evaluating the clinical response using the Knee Injury and Osteoarthritis Outcome Score questionnaire, miR‐451 and miR‐15b expression levels were detected using real‐time polymerase chain reaction. The serum levels of CXCL16 and BCL‐2 were evaluated using enzyme‐linked immunosorbent assay kits before (time zero) and after treatment (month four). Results Metformin increased miR‐451 expression levels simultaneously with pain reduction, whereas miR‐15b expression did not change significantly after four months of treatment. Also, metformin decreased the serum levels of BCL‐2 and CXCL16 in patients with OA. Conclusion The effects of metformin in reducing pain can be attributed to many factors, including its anti‐inflammatory and antiaging effects. Our findings suggest that metformin may reduce pain and inflammation in patients with OA through the regulation of miR‐451/CXCL16 and BCL‐2.